Book Reviews. (1st December 2009) - Aitsiselmi, Farid; Beauquis, Corinne; Brning, Angela; Narbona, Inmaculada Daz; Forsdick, Charles; Frith, Nicki; Gyssels, Kathleen; Knepper, Wendy; Matzke, Christine; Oktapoda, Efstratia; Poole, Sara; Tarr, Carrie
Transition and Development in Algeria: economic, social and Cultural Challenges, Margaret Majumdar and Mohammed Saad (2005) Bristol: Intellect books, 192 pp., ISBN 9781841500744, Paperback, 19.95Traduction et enjeux identitaires dans le contexte des Amriques, (ed.) Louis Jolicur (2007) Qubec: Presses de l'Universit Laval, 194 pp., ISBN 978-2-7637-8547-9, Paperback, $30Signs of Dissent: Maryse Cond and Postcolonial Criticism, Dawn Fulton (2008) Charlottesville and London: University of Virginia Press, 190 pp., ISBN 978-0-8139-2715-2, Paperback, $20criture en transhumance entre Maghreb et Afrique subsaharienne. Littrature, oralit, arts visuels, Hlne Tissires (2007) Paris: L'Harmattan, 293 pp., ISBN 978-2-296-02794-7, Paperback, 27.50 The Fanon Reader, Azzedine Haddour (ed.), (2006) London: Pluto Press, xxv 206 pp., ISBN 0-7453-1560-7, Paperback, 16.99The French Atlantic Triangle: Literature and Culture of the Slave Trade, Christopher L. Miller (2008) Durham, NC: Duke University Press, 571 pp., ISBN 978-0-8223-4151-2, Paperback, $27.95Simone Schwarz-Bart dans la potique du rel merveilleux. Essai sur l'imaginaire antillais, Mariella Aita (2008) Paris: L'Harmattan, 278 pp., ISBN: 9-782296 070059, Paperback, 26.50The Black Renaissance in Francophone African and Caribbean Literatures, K. Martial Frindthi (2008) Jefferson and London: McFarland, 209 pp., ISBN 978-0-7864-3663-7, Paperback, 34.50Im Auge des Gesetzes: Kriminalromane aus dem frankophonen Afrika sdlich der Sahara Gattungskonventionen und Gewaltlegitimation, Katja Meintel (2008) Aachen: Shaker, 264 pp., ISBN 978-3-8322-5830-6, Paperback, 45.80; PDF download at www.shaker.de, 4.58Songes briss; Paroles clates; Le blanc de la parole, Najib Redouane, Posies (2008) Montral: Les ditions du Marais, trois volumes, 66 pp., ISBN 978-2-9809859-4-2 (pbk), 66 pp., ISBN 978-2-9809859-3-5 (pbk), 65 pp., ISBN 978-2-923721-00-2 (pbk), $15 CADOn Evelyne Accad. Essays in Literature, Feminism, and Cultural Studies, Cheryl Toman (ed.), (2007) Birmingham, Alabama: Summa Publications, 420 pp., ISBN 978-1-883479-53-4, Hardback, $58 USRemembering the (Post) Colonial Self. Memory and Identity in the Novels of Assia Djebar, Jenny Murray (2008) Oxford/Bern/Berlin/Bruxelles/Frankfurt am Main/New York/Wien: Peter Lang, 258 pp., ISBN 978-3-03911-367-5, Paperback, 31Algeria Cuts. Women and Representation, 1830 to the present, Ranjana Khanna (2008) Stanford, California: Stanford University Press, 301 pp., ISBN 978-0-8047-5262-6 (pbk), 17.50